Trans* necropolitics. Gender Identity Law in Argentina - Martin De Mauro Rucovsky
On May 9th, 2012, the Argentinean Senate converted into law the long collective process, driven by trans* activism, towards the legal recognition of gender identity. The Gender Identity Act (GIA) meant a large contribution to the field of civil and sexual rights interationally, especially in the matter of trans* policy. Nevertheless, what was at stake in the approval of the GIA was not just a step forward in legal terms and at a personal level for trans* people, but a whole set of representations, desires and social stakes on trans* lives and population. Thus, as regards to the scope and achievements of the GIA and its social and parliamentary debates, we can assert that in that realm a specific trans* life does not qualify as a living life. This article addresses the specific ways of presentation and apprehension of trans* lives in parliamentary debates about the GIA, and in social disputes within trans* activism. A biopolitical analysis of gender identity leads us to rethink the social conditions that sustain life and, by the same token, the interpretative frameworks of death.